Leishmanial antigens in the diagnosis of active lesions and ancient scars of American tegumentary leishmaniasis patients - Schubach, Armando; Cuzzi-Maya, Tullia; Oliveira, Albanita V; Sartori, Alexandrina [UNESP]; Oliveira-Neto, Manoel P. de; Mattos, Marise S; Araújo, Marcelo Lodi; Souza, Wilson Jacinto S.; Haddad, Fátima; Perez, Maurício de A.; Pacheco, Raquel S.; Momen, Hooman; et al. (Instituto Oswaldo Cruz, Ministério da Saúde, 2001)
Cutaneous biopsies (n = 94) obtained from 88 patients with American tegumentary leishmaniasis were studied by conventional and immunohistochemical techniques. Specimens were distributed as active lesions of cutaneous leishmaniasis (n = 53) (Group I), cicatricial lesions of cutaneous leishmaniasis (n = 35) (Group II) and suggestive scars of healed mucosal leishmaniasis patients (n = 6) (Group III). In addition, active cutaneous lesions of other etiology (n = 24) (Group C1) and cutaneous scars not related to leishmaniasis (n = 10) (Group C2) were also included in the protocol. Amastigotes in Group I biopsies were detected by routine histopathological exam (30.2%), imprint (28.2%), culture (43.4%), immunofluorescence (41.4%) and immunoperoxidase (58.5%) techniques; and by the five methods together (79.3%). In Group II, 5.7% of cultures were positive. Leishmanial antigen was also seen in the cytoplasm of macrophages and giant cells (cellular pattern), vessel walls (vascular pattern) and dermal nerves (neural pattern). Positive reaction was detected in 49 (92.5%), 20 (57%) and 4 (67%) biopsies of Groups I, II and III, respectively. Antigen persistency in cicatricial tissue may be related to immunoprotection or, on the contrary, to the development of late lesions. We suggest that the cellular, vascular and neural patterns could be applied in the immunodiagnosis of active and cicatricial lesions in which leishmaniasis is suspected.
Keywords: American tegumentary leishmaniasis; Leishmania (Viannia) braziliensis; immunodiagnosis; scar; cured patients